Development of E-Earning Learning Media Based on the Kahoot Application in Geography Subjects - Potutu, Sri Dewi; Maryati, Sri; Yusuf, Daud (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Learning media is a very important component of learning resources in the learning process. This research aims to develop e-learning media based on the Kahoot application in geography subjects regarding rural and urban spatial interactions. This research uses the ADDIE development research method which consists of five stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The research results showed that the media expert validation score was 85%, the material expert validation score was 83%, the teacher validation score was 85%, and the average student response score was 97.81%. The scores resulting from validation by experts and the student response scores show that the Kahoot-based Elearning learning media in the geography subject on topic of Village and City Spatial Interaction is categorized as very valid and suitable for use in the learning process.